Flame-retardant MXene/polyimide film with outstanding thermal and mechanical properties based on the secondary orientation strategy. Issue 19 (1st September 2021) - Zhu, Yue; Zhao, Xingbin; Peng, Qingyu; Zheng, Haowen; Xue, Fuhua; Li, Pengyang; Xu, Zhonghai; He, Xiaodong
Abstract : A three-dimensional foam is fabricated to enhance the interfacial interaction between adjacent MXene sheets and polyimide (PI) macromolecules; then a composite film with a dense and well-ordered layer-by-layer structure, good flexibility and flame retardancy is produced. Abstract : With the development of multifunction and miniaturization in modern electronics, polymeric films with strong mechanical performance and high thermal conductivity are urgently needed. Two-dimensional transition metal carbides and nitrides (MXenes) have attracted extensive attention due to their tunable surface chemistry, layered structure and charming properties. However, there are few studies on using MXenes as fillers to enhance polymer properties. In this paper, we fabricate a three-dimensional foam by the freeze-drying method to enhance the interfacial interaction between adjacent MXene sheets and polyimide (PI) macromolecules, and then a composite film with a dense and well-ordered layer-by-layer structure is produced by the hot-pressing process. Based on the secondary orientation strategy, the resultant MXene/PI film exhibits an enhanced thermal conductivity of 5.12 ± 0.37 W m −1 K −1 and tensile strength of 102 ± 3 MPa. Moreover, the composite film has good flexibility and flame retardancy owing to the synergistic effect of MXene sheets and PI chains. Hence, the MXene/PI composite film with the properties of flexibility, flame-retardancy, high mechanical strength and efficient heat transmission is expected to be used as the next thermal management material in a variety of applications.